Vegetative propagation of trees in the 1980s - Longman, K (Commenwealth Forestry Institute, University of Oxford, 1981)
Extended Summary of a meeting at Merrist Wood Agricultural College, Worplesdon, near Guildford, Surrey, England. February 19-20, 1981